Guide to the Liverworts of North Carolina - Hicks, Marie L. (Book collections on Project MUSE., 1992)
North Carolina is home to 66 genera and 195 species of liverworts--small, mosslike plants occupying moist microhabitats that form an inconspicuous part of the vegetation. Marie L. Hicks' Guide to the Liverworts of North Carolina provides the first complete field guide to the hepatic flora in North Carolina. The volume offers a key to genera, species descriptions, distribution maps, a glossary, and 120 original drawings of liverworts as they appear in North Carolina.North Carolina's varied physiography creates a diversity of flora, ranging from boreal plants in the mountains to subtropical plants in the coastal plain. Collections of hepatics in North Carolina have been sporadic over the years, and knowledge of their distribution within the state has accumulated gradually. Guide to the Liverworts of North Carolina builds on earlier field studies, including those of Hugo L. Blomquist and R. M. Schuster, to provide keys and illustrations to aid identification. This important, comprehensive field guide will also be useful in states adjoining North Carolina and is designed for students, botanists, and all those interested in identifying local liverworts.